Hubungan Pola Makan dengan Kadar Hb Pada Ibu Hamil Trimester I di Puskesmas Anak Air Kota Padang Tahun 2025 - Nia Afnita Rizana; Hasanalita Hasanalita; Yen Risa Sanputri; Indri Putri Sari; Yofa Sukmawati; Chyka Febria (Jurnal Ners, 2026)
In Indonesia, 41.8% of maternal deaths are caused by anemia during pregnancy. The prevalence of anemia in West Sumatra is 17.38%. In Padang City, the prevalence of anemia in Padang City is 43%. One of the factors that can cause anemia during pregnancy is diet. The purpose of this study was to determine the relationship between diet and Hb levels in pregnant women at the Anak Air Health Center in Padang City in 2025. The type of analytical research was cross-sectional design. The independent variable was diet and the dependent variable was Hb levels. The study population was 38 pregnant women in the first trimester. The sampling technique was Total Sampling. Data collection was by questionnaire and observation. The study was conducted in March 2025 at the Anak Air Health Center. Data processing and data analysis were carried out using the Chi Square test. The results showed that the frequency of respondents' Hb levels showed that some respondents experienced anemia, namely 16 people (57.9%). Respondents had poor diets, namely 17 people (44.7%). The statistical test results obtained a p-value of 0.010 (p-value <0.05), indicating a significant relationship between diet and hemoglobin levels. Diet affects hemoglobin levels in pregnant women. This study is expected to increase respondents' knowledge and insight, provide information for other researchers, and provide evaluation for Community Health Centers.